The native cell population does not contribute to central‐third graft healing at 6, 12, or 26 weeks in the rabbit patellar tendon. Issue 4 (8th November 2012) - Kinneberg, Kirsten R.C.; Galloway, Marc T.; Butler, David L.; Shearn, Jason T.
Abstract Investigators do not yet understand the role of intrinsic tendon cells in healing at the tendon‐to‐bone enthesis. Therefore, our first objective was to understand how the native cell population influences tendon autograft incorporation in the central‐third patellar tendon (PT) defect site. To do this, we contrasted the histochemical and biomechanical properties of de‐cellularized patellar tendon autograft (dcPTA) and patellar tendon autograft (PTA) repairs in the skeletally mature New Zealand white rabbit. Recognizing that soft tissues in many animal models require up to 26 weeks to incorporate into bone, our second objective was to investigate how recovery time affects enthesis formation and graft tissue biomechanical properties. Thus, we examined graft structure and mechanics at 6, 12, and 26 weeks post‐surgery. Our results showed that maintaining the native cell population produced no histochemical or biomechanical benefit at 6, 12, or 26 weeks. These findings suggest that PTA healing is mediated more by extrinsic rather than intrinsic cellular mechanisms. Moreover, while repair tissue biomechanical properties generally increased from 6 to 12 weeks after surgery, no further improvements were noted up to 26 weeks. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 638–644, 2013